Legacies of domestication, trade and herder mobility shape extant male zebu cattle diversity in South Asia and Africa. Issue 1 (December 2018) - Pérez-Pardal, Lucía; Sánchez-Gracia, Alejandro; Álvarez, Isabel; Traoré, Amadou; Ferraz, J.; Fernández, Iván; Costa, Vânia; Chen, Shanyuan; Tapio, Miika; Cantet, Rodolfo; Patel, Ajita; Meadow, Richard; et al.
Abstract All tropically adapted humped cattle (Bos indicus or "zebu"), descend from a domestication process that took place >8, 000 years ago in South Asia. Here we present an intercontinental survey of Y-chromosome diversity and a comprehensive reconstruction of male-lineage zebu cattle history and diversity patterns. Phylogenetic analysis revealed that all the zebu Y-chromosome haplotypes in our dataset group within three different lineages: Y3A, the most predominant and cosmopolitan lineage; Y3B, only observed in West Africa; and Y3C, predominant in South and Northeast India. The divergence times estimated for these three Zebu-specific lineages predate domestication. Coalescent demographic models support eitherde novo domestication of genetically divergent paternal lineages or more complex process including gene flow between wild and domestic animals. Our data suggest export of varied zebu lineages from domestication centres through time. The almost exclusive presence of Y3A haplotypes in East Africa is consistent with recent cattle restocking in this area. The cryptic presence of Y3B haplotypes in West Africa, found nowhere else, suggests that these haplotypes might represent the oldest zebu lineage introduced to Africa ca. 3, 000 B.P. and subsequently replaced in most of the world. The informative ability of Interspersed Multilocus Microsatellites and Y-specific microsatellites to identify genetic structuring in cattle populations is confirmed.